Social Return On Investment (SROI) Program Tanggung Jawab Sosial Dan Lingkungan (TJSL) BUMN Tahun 2024 - Rina Ekawati; Ari Djanuar Prasetyo; Suesilowati Suesilowati (Jurnal Minfo Polgan, 2024)
The SROI Environmental Social Responsibility Program aims to measure the impact of the GBK Ecofoodcourt empowerment program. The research method used is qualitative causality. Primary data collection techniques through in-depth interviews and secondary results of program fund monetization. In general, the GBK Ecofoodcourt Development Program has enormous benefits in improving the welfare of UMKM managers and their employees. The SROI value of the GBK Ecofoodcourt Development Program reached a value of 2.75, which means it is greater than 1. The meaning of this ratio value is that the program has an optimal positive impact on the beneficiaries.